IMPLEMENTASI HUKUM DAN HAK ASASI MANUSIA DI INDONESIA - Nirwansyah, Nirwansyah (Jurnal Ipteks Terapan, 2014)
Ensure legal certainty in the community, is to publish or assign relevant laws. Law is a rule in the form of norms and sanctions, created with the purpose of regulating human behavior, maintain order, justice, and prevent chaos. Each masyarat, is entitled to obtain a defense before the law. Law can be interpreted as a statute or statutes / regulations written or unwritten to regulate peoples lives and provide sanctions for violating it. Man, born in any parts of the world, legally own rights to live. Enforcement of Human Rights (HAM), irrespective of economic status, education, gender, race and other. The concept of human rights, which spearheaded UN Human Rights Commission of Human Rights gave birth to seventeen points stated in the declaration. The declaration or agreement "Universal Declaration of Human Rights" has been ratified by the Indonesian government through Law No. 39 of 1999 on Human Rights. The spirit of this law, is to exalt the dignity, the dignity of the nation in the hope away from the offense. Because the real human rights will not be traded, and can not mebatasi others outside corridor applicable law. Human rights perspective in the community, is still far from the expected. Legal product is considered to have many loopholes that affect law enforcement is not working as it should. Increased commitment of the Indonesian government in realizing human rights enforcement in the future, is expected to be more serious As social beings, should be able defend themselves and fight for their rights. Furthermore, it should be able to respect and preserve the rights of others. The government has time to open your eyes wide to be cases of human rights violations in Indonesia, or Indonesian citizens abroad.Doi: 10.22216/jit.2014.v8i4.10